ANALISIS PERKEMBANGAN BELAJAR GERAK SISWA SEKOLAH DASAR DALAM PEMBELAJARAN PJOK - Radzy Ayyubi Nasution; Deardo Febrian Saragih; Christian Elka Ginting; Abdul Rahman; Elsa Fitria Pulungan; Amansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the development of elementary school students' movement learning in Physical Education, Sports, and Health (PJOK) learning. Movement learning is a process of changing movement abilities acquired through continuous practice and experience. At elementary school age, the development of movement learning becomes an important aspect because it is related to the mastery of basic movement skills, including locomotor, non-locomotor, and manipulative movements. This study used a literature study method (library research) with a qualitative descriptive approach. Data were obtained from various journal articles, books, and scientific sources relevant to the topic of movement learning development and PJOK learning. Data collection was carried out through a literature search using Google Scholar with keywords: movement learning, motor development, basic movement, PJOK learning, and elementary school students. Data analysis was carried out using content analysis techniques through the stages of data collection, reduction, presentation, and drawing conclusions. The results of the review of eight journals indicate that students' movement learning development can be improved through the use of active, varied, and game-based learning models. Game-based learning has been proven to improve basic movement skills, locomotor abilities, participation, motivation, and student learning outcomes. Furthermore, the use of engaging learning media and cooperative activities also positively impacts the development of students' motor skills. Therefore, physical education (PJOK) instruction plays a crucial role in supporting the development of elementary school students' motor skills. Therefore, teachers need to implement innovative learning strategies tailored to student characteristics to ensure optimal motor skills development.